HOTS MATHEMATICS TEST FOR JUNIOR HIGH SCHOOL STUDENTS: CONTENT VALIDITY ANALYSIS - Lovieanta Arriza; Zafrullah Zafrullah; Retnawati, Heri; Debi Pranata; Rama Angger Wibowo; Ilham Kandari (Mathematics Research and Education Journal, 2025)
This study aims to analyze the content validity of the HOTS mathematics test for the seventh-grade students at junior high school. The HOTS test instrument is an instrument which is developed from Core Competencies and Basic Competencies and also adapted to HOTS indicators based on Bloom's taxonomy which includes the levels of analyzing (C4), evaluating (C5) and creating (C6) which are then formulated into 5 test item descriptions. The method of this research is a descriptive analysis method as content validity analysis based on the calculation of Aiken's V formula. Content validity data were obtained from six experts from various fields, namely mathematics education lecturers, assessment and measurement experts, and junior high school mathematics teachers. The expert validation results were calculated by using Aiken's V formula. The five test items that had been compiled were declared “valid” with details of four items having an Aiken's index of 1.00 and the remaining one item having an Aiken's index coefficient of 0.96. This quantitative assessment provides an illustration that the mathematics test instrument that has been developed is valid and can be used to measure the HOTS abilities of the seventh-grade students at junior high school.